The Analysis Of Learners’ Need Of Task-Based Handout For Learning Academic Writing Academic Writing Of The Fourth Semester Students In Stiba Persada Bunda - Vilma Okimura; Hermawati Syarif; Zul Amri (International Journal of Educational Dynamics, 2020)
This study aimed at investigating need of task-based handouts for learning academic writing for the fourth semester in STIBA Persada Bunda Pekanbaru. To achieve the aim, the researcher distributed questionnaire and conducted interview. The data of this research were two, qualitative and quantitave data. Qualitative data was analyzed descriptively, while quantitative data was analyzed by using formula and likert scale. The result showed that provided material of academic writing did not fullfil the learners’ need of material. The provided material presented the material of academic writing in complicated explanation, while the learners need the material in simple and understandable presentation. Thus, the analysis result showed that task-based handouts was needed by learners.